Small and historic towns in Zabaikalye: Borzya - Kradin, Nikolai (project baikal, 2021)
Based on historical and archival materials and on-site studies of the author, the article discusses the architecture of Borzya, one of the small towns of Transbaikalia, which has a rich history and monuments of culture and nature, which are of great interest not only to researchers, but also residents of Transbaikalia, as well as guests of this unique territory. Among such unique monuments are the Konduiskoye settlement, the Church of the Nativity of the Blessed Virgin Mary, Salt Lake and other no less interesting objects.